PEMBUATAN ALAT PENGEPRES BIJI MELINJO SEBAGAI TEKNOLOGI TEPAT GUNA UNTUK MENGOLAH BIJI MELINJO MENJADI EMPING - Sari, Mayang; Yanto, Subari; Yahya, Muhammad (Jurnal Pendidikan Teknologi Pertanian, 2016)
The aims of this research is to design a pressing tool melinjo’s grain and to know the results of testing pressing tool melinjo’s grain to process the melinjo’s grain into the chips.  The research is the engginering research and design. Research data obtained from testing tool by calculation pressing pressure, the capacity of working tools, the percentage of damaged materials and measurements of the thickness of  melinjo’s chip. The technique of  data analysis using quantitative analysis with descriptive of statistic. Based on the results of the calculation, pressure of pressing tool melinjo’s grain must be greater than 2,6 kg/cm2, the working capacity of tool must product average percentage 0,173 kg/h, the percentage of materials damage has average percentage 40,29 % and thickness measurement of chip has the best thickness on the 3rd testing with average thickness 1,208 mm